Features of modern organization management when implementing a digital transformation strategy - A. V. Zheregelya (Вестник университета)
The article examines the factors that determine the features of organization management in the process of implementing the digital transformation strategy in modern conditions, and gives their assessment. The results of a survey of employees on the issue of readiness to work in a digital environment when business processes change are presented. The conditions for the development of digital transformation of a modern organization and the work of personnel, as well as positive and negative factors determining the proliferation of this process are analyzed. The aspect of the institutional field of the new management paradigm, which determines the resilience of new formats of professional activity in the emerging digital reality, is touched upon. It is concluded that the process of digital transformation as a new management paradigm, which, unlike traditional approaches, involves a fundamental restructuring of the existing structure, business processes, organizational and managerial mechanism of interaction with all stakeholders and provides transformation of the organization by revising the culture, strategy, models, operations, products, marketing, goals, including employee management. In turn, this will require, on the one hand, the transformation of the technologization process of management, intensifying interaction with personnel and creating effective communication channels, on the other hand, the cascadability of management processes that form other methods of this interaction, having a positive impact on both the effectiveness of managerial, economic and organizational processes, and on a quality solution of specific tasks.